1993
DOI: 10.1212/wnl.43.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term and high‐dose piracetam treatment of Alzheimer's disease

Abstract: Preclinical research suggests that piracetam (a nootropic drug) may improve cognitive functions, but previous studies have failed to demonstrate a clear benefit for the treatment of Alzheimer's disease (AD). We report a 1-year, double-blind, placebo-controlled, parallel-group study with a high dose of piracetam (8 g/d per os) in 33 ambulant patients with early probable AD. Thirty subjects completed the 1-year study. No improvement occurred in either group, but our results support the hypothesis that long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 0 publications
2
51
0
3
Order By: Relevance
“…Piracetam, a commonly used nootropic has been tried for management of AD with poor results. It has shown to slow the progression of cognitive deterioration at high-dose and long-term treatment in humans [35] . Cochrane review published in 2001 did not support the use of piracetam in management of AD [36] .…”
Section: Role Of Cognition Enhancers (Nootropics)mentioning
confidence: 99%
“…Piracetam, a commonly used nootropic has been tried for management of AD with poor results. It has shown to slow the progression of cognitive deterioration at high-dose and long-term treatment in humans [35] . Cochrane review published in 2001 did not support the use of piracetam in management of AD [36] .…”
Section: Role Of Cognition Enhancers (Nootropics)mentioning
confidence: 99%
“…This favorable pharmacological profile stimulated the investigation of the potential antiamnesic activity of nootropics in human neurodegenerative pathologies. Nevertheless, results from controlled clinical trials have questioned the usefulness of nootropic compounds for treatment of cognitive disorder in humans [Sarter, 1991], several studies have demonstrated their usefulness for the treatment of cognitive impairment in the elderly [Vernon and Sorkin, 1991], in mild to moderate dementia [Chouinard et al, 1983;Nicholson, 1990], in Alzheimer's disease [Croisile et al, 1993;Parnetti et al, 1997], and for the treatment of cognitive deficit in early Parkinsonism [Oepen et al, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have focused on cognition enhancement and memory improvement by nootropic drugs. Some pyrrolidone derivatives, such as piracetam, aniracetam and oxiracetam, ameliorate the condition of elderly patients suffering from mild to moderate mental deterioration (Chouinard et al 1983;Maina et al 1989;Nicholson 1990;Vernon and Sorkin 1991;Lee and Benfield 1994), of geriatric patients with cerebrovascular insufficiency (Foltyn et al 1983), in Alzheimer's disease (Senin et al 1991;Croisile et al 1993;Parnetti et al 1997) and are useful in the treatment of cognitive deficits in early Parkinsonism (Oepen et al 1985).…”
Section: Introductionmentioning
confidence: 99%